STATE AND CIVIL SOCIETY: G.W.F. HEGEL CONCEPTION ON THE STATE’S CONSTITUTION - Linda Sudiono (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractThis study aims to discuss the relationship between State and Civil Society according to G.W.F. Hegel and its implications towards the formation of State and Law. This study is expected to result critiques of Hegel's state and civil society conception as this conception has been implemented in Indonesia through Integralistic concept. The method of this study is normative study with discourse analysis through critical approach. The result shows Hegel’s view of the relationship between Civil Society and State (including its Constitutional Laws) focuses on the dialectical interaction between the particularity of Civil Society and the universality of State. IntisariTujuan dari penelitian ini adalah untuk mendiskusikan tentang hubungan antara Negara dan Masyarakat Sipil menurut G.W.F. Hegel dan implikasinya terhadap pembentukan Negara dan Hukum. Studi ini diharapkan menghasilkan kritik terhadap konsepsi negara dan masyarakat menurut Hegel, yang pernah diterapkan di Indonesia melalui konsep Integralist. Metode penelitian ini adalah penelitian normatif dengan analisis wacana melalui pendekatan kritis. Hasilnya menunjukkan pandangan Hegel tentang hubungan antara Masyarakat Sipil dan Negara (termasuk Hukum Konstitusionalnya) berfokus pada interaksi dialektis antara kekhususan Masyarakat Sipil dan universalitas Negara.